Church and State in Conflict Over The Establishment Protestant Church - Putri, Rizca Yunike; Sufaidi, Ahmad; Rahmawati, Silvi; Fikana, Novita Sari; Dauhan, Angellina Parasyati; Irawan, Wika Tata; Hutapea, Petrus Putera Anggara; Putry, Rizky Pangestuty Mileniandry (Journal of Urban Sociology, 2024)
A series of incidents involving places of worship are still widespread in Indonesia. In recent years, the construction of places of worship has become an interesting problem not only in the social context of interaction between religious communities but also conflict resolution in Indonesia. Minority religious groups tend to have difficulty establishing or renovating their places of worship because they receive pressure and intervention from the majority group. This research explores the issue of residents' rejection and closing and stopping the process of building a house of worship for the HKBP Efrata Church in Gresik Regency, East Java. The aim of this research is to describe the things that trigger conflict and analyze the conflict resolution mechanism of the HKBP Efrata Driyorejo Gresik church. This research uses a qualitative-descriptive method, namely a research effort based on methodology in studying the phenomenon of conflict over places of worship at the HKBP Efrata Driyorejo Gresik Church. It is known that the church was prohibited from carrying out worship activities by local residents for approximately 6 (six) years due to problems with permits to carry out worship in the area. After receiving permission, disturbances often arise when the congregation performs their worship, such as noise coming from motorized vehicles and restrictions on the worship schedule given by local residents.Keywords: church founding conflicts, gereja HKBP Efrata Gresik, religious house building regulations, religious house conflicts